Temperature dependence of the magnetic phase transitions of CoCIZ 2H 2O - Lowe, M.; Abeledo, Carlos R.; Misetich, A. A. (American Chemical Society's, 1971)
Fil: Lowe, M.. Comisión Nacional de Energía Atómica; Argentina